Influence of coping strategies and gender on relationships between personality traits and test anxiety among high school students in Iran - Asghari, Arezou (2013)
The purpose of this study is to examine the mediating role of coping strategies and moderating role of gender on the relationship between personality traits and test anxiety among Iranian high school students in Iran. The respondents of the study were 375 high school students (193 males, 182 females) aged 15-18. They were selected by random cluster sampling method from 6 public high schools in Gorgan city, Iran. The participants responded to a brief demographic questionnaire and four valid and reliable questionnaires including the NEO-FFI-3 (McCrae & Costa, 1992), the trait anxiety inventory (TAl, Spielberger et al., 1980), the cope inventory (COPE; Carver, Scheier, & Weintraub, 1989), and the state anxiety inventory (STAI, Form Y 1, Spielberger, 1983). The study recruited a quantitative method with cross-sectional design. The researcher sought to examine the relationship between personality traits and test anxiety as well as the mediation role of coping strategies on the relationship between personality traits and test anxiety. Furthermore, it sought to examine the moderating role of gender on the relationship between personality traits and test anxiety. Data analysis included frequencies, percentages, mean and standard deviation, structural equation model (SEM) for validity of the instruments, and both mediational and moderation analysis. Findings revealed that from personality dimensions, neuroticism had a positive significant relationship with test anxiety while extraversion and conscientiousness had negative significant relationship with test anxiety. Yet, agreeableness and openness did not show any significant relationships to test anxiety. Furthermore, trait anxiety showed positive significant relationship with test anxiety. Mediation analyses indicated that problem-focused coping mediated the relationship between extraversion, and neuroticism with test anxiety but it did not mediate the links between agreeableness, conscientiousness, openness and trait anxiety with test anxiety. Emotion-focused coping merely mediated the relationship between trait anxiety and test anxiety but it failed to mediate other personality dimensions. Finally, avoidant coping mediated the links between extraversion and neuroticism with test anxiety but it failed to mediate the paths between other personality dimensions with test anxiety. In addition, it mediated the link between trait anxiety and test anxiety. Lastly, results illustrated that gender moderated the paths between two personality dimensions including, extraversion and conscientiousness with test anxiety but it did not moderate the paths between other personality dimensions and also trait anxiety with test anxiety. Results of the study substantiated that coping dimensions mediated several paths between personality traits and test anxiety. Thus, it has clear directions and applications for clinicians, school psychologist and counselors, and other health workers to perceive the patterns of coping in Iranian high school students prior to any intervention or treatment programs.